Teacher interaction networks and system maintenance : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Education - Halliday, Terence Charles (Massey University, 1972)
Theoretical Considerations Since the study of Hoppock in 1935 a great deal of attention has been shown In the analysis of job satisfaction of workers and personnel in a variety of situations within organisations. This concern has important theoretical and pragmatic considerations. Theoretically, satisfaction is linked to the more general problem of explaining social system persistence and existence. The sociologist is interested to address himself to at least two questions: what were the conditions under which the social system emerged; and under what conditions is it maintained as a viable system? It is the latter question which has particularly concerned the functionalist tradition for the last century. The functionalists - from Durkheim to Parsons - applied the analogy of biological organisations to their explanation of social phenomena. They maintained that even as the biological system has a certain degree of functional interdependence and responsiveness to the external environment so too the social system can be seen as generating structure in response to certain functional problems. They argued, at least implicitly, that the social system was more or less functionally analogous to a biological organism. However there are severe limitations to this argument. Nagel (1961) has argued that any functional analysis must satisfy five criteria: system boundaries are to be specified; the embedding environment must be isolated; the system elements must be specified; the necessary conditions or the system requirements must be understood; and finally a goal state or criterion needs to be established. In biological organisms these conditions are relatively easily met. The organism is clearly specifiable. Organisms for tho most part have clearly designated states which either are or are not maintained. In most cases therefore it is possible to specify with a high degree of accuracy certain components of the organism and its various states. "In consequence, since the system and the state can be clearly defined in biology, it is intelligible to ask, and seek an answer by way of experimental enquiry,. whether and by what mechanisms, System S is maintained in State G". [FROM INTRODUCTION]
Keywords: Teachers